Day-4 antipseudomonal and anti-MRSA de-escalation was not associated with higher mortality in critically ill patients with sepsis - Yuhang Zhang; Guoying Liao; Jianli Song; Yinsheng Liao; Lulu Zhang (Frontiers in Medicine, 2026)
Background Broad empiric antibiotics are often appropriate at the start of intensive care unit (ICU) sepsis care; however, continued antipseudomonal or anti-methicillin-resistant Staphylococcus aureus (MRSA) coverage may no longer be justified by the day-4 reassessment. We examined antibiotic de-escalation at this clinical decision point. Materials and methods We emulated two parallel target trials in Medical Information Mart for Intensive Care IV (MIMIC-IV) v3.1 and conducted a supportive multicenter analysis in the eICU Collaborative Research Database (eICU-CRD) v2.0. The strict MIMIC-IV cohort included patients with ICU sepsis, early receipt of broad-spectrum antibiotics, survival and continued observation through 96 h, available culture information before time zero, no recorded multidrug-resistant organism evidence, and no prespecified exclusions. Time zero was 72 h after antibiotic initiation; exposure was classified during 72–96 h, and follow-up began at 96 h. Trial A compared anti-MRSA de-escalation with continuation, and Trial B compared antipseudomonal de-escalation with continuation. Propensity scores, overlap weighting, and bootstrap confidence intervals were used. Results The strict MIMIC-IV cohort included 5,762 patients. In Trial B, 1,569 patients were de-escalated, and 3,070 continued antipseudomonal coverage. De-escalation was associated with lower 30-day mortality (24.1% vs. 29.0%; risk difference, −4.91 percentage points; 95% confidence interval, −7.27 to −2.23), lower in-hospital death, lower stage 2–3 acute kidney injury, and more death-adjusted antibiotic-free days. In Trial A, 3,041 patients were de-escalated, and 1,728 continued anti-MRSA coverage; there was no evidence of higher 30-day mortality (26.3% vs. 27.8%; risk difference, −1.44 percentage points; 95% confidence interval, −3.75 to 1.11), and de-escalation was associated with more antibiotic-free days. In eICU-CRD, Trial B showed a directionally consistent association with lower hospital mortality (10.2% vs. 12.7%; cluster-bootstrap risk difference, −2.42 percentage points; 95% confidence interval, −3.87 to −0.87). Conclusion Day-4 de-escalation was not associated with higher mortality and was accompanied by reduced antibiotic exposure. The lower mortality and kidney-injury estimates in Trial B are exploratory because de-escalation may mark early recovery that is incompletely captured in structured data. The eICU-CRD analysis provides directional support rather than formal external validation. Prospective evaluation is warranted.